Real-world use of inotuzumab ozogamicin is associated with lower health care costs than blinatumomab in patients with acute lymphoblastic leukemia in the first relapsed/refractory setting - Alexander Russell-Smith; Louise Murphy; Amy Nguyen; Cori Blauer-Peterson; Marilou Terpenning; Feng Cao; Shiqiang Li; Tim Bancroft; Noah Webb; Stephanie Dorman; Richa Shah (Becaris Publishing Limited, 2023)
Aim: To compare all-cause and acute lymphoblastic leukemia (ALL)-related healthcare resource utilization (HCRU) and costs among patients receiving inotuzumab ozogamicin (InO) and blinatumomab (Blina) for ALL in the first relapsed/refractory (R/R) setting. Patients & methods: We studied retrospective claims for adult commercial and Medicare Advantage enrollees with ALL receiving InO (n = 29) or Blina (n = 23) from 1 January 2015 to 16 February 2021. Mean per-patient-per-month (PPPM) HCRU and total costs were described and multivariable-adjusted PPPM total all-cause and ALL-related predicted costs were calculated. Results: Mean monthly ALL-related hospitalizations were the same for patients receiving InO and Blina (PPPM = 0.8 stays); however, the length of ALL-related hospital stay was almost twice as long among patients receiving Blina versus InO (ALL-related: InO = 7.6 days; Blina = 14.1 days; p = 0.346). In multivariable models, total ALL-related costs were 43% lower for InO compared with Blina (PPPM costs: InO = $93,767; Blina = $163,470; p = 0.021). Conclusion: In the first R/R setting, patients who used InO had significantly lower all-cause and ALL-related costs compared with patients who used Blina, in part driven by hospitalization patterns.